Análise da produção vitivinícola no município de São Roque-SP - Carvalho, Joice Maria Rodrigues Máximo de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The São Paulo State grape-wine culture has been structured from the conditions beforehand by the coffee production in different areas of the State and formed later the grape-wine culture region in the area of Jundiaí and São Roque. In the latter, conditions for the development of the activity started from the expansion of the Sorocabana Railway, from the immigration and the consequent growing of the town. Government improvements and the locals getting more involved to this activity showed, in the 1950s, a qualitative development of the grape-wine culture, so that larger industries established in the area, what counters the production years before, which was supported by small properties and family work. Nowadays, calls attention the changes done on the production process also the public departments participation searching for development of the area, trying to confirm the historical identity and performing advances in the production techniques, further market insertion, reinforcing the local tradition on viticulture, that is an important strategy for competitiveness, articulating the grape-wine culture production to other sections of economy, especially tourism.

A produção vitivinícola paulista se estruturou a partir das condições propiciadas pela produção do café, em diversas áreas do Estado de São Paulo, formando, posteriormente, pólos de vitivinicultura nos municípios de Jundiaí e São Roque. Nesta última cidade, as condições para o desenvolvimento da atividade surgiram a partir da expansão da Estrada de Ferro Sorocabana, da imigração e do consequente crescimento do município. A partir do fomento dos órgãos estaduais e do maior envolvimento local com a atividade, pôde-se observar, na década de 1950, o desenvolvimento qualitativo da produção vitivinícola, com o estabelecimento de indústrias de porte maior, diferentemente da produção das décadas anteriores, baseada na pequena propriedade e no trabalho familiar. Atualmente, destacamse as mudanças incorporadas ao processo produtivo das mesmas, além da participação dos órgãos públicos na busca pelo desenvolvimento do setor, tentando confirmar sua identidade histórica e desenvolvendo melhorias nas técnicas de fabricação, além de uma maior inserção no mercado, reforçando a tradição local em torno da vitivinicultura, o que constitui uma estratégia importante na busca por competitividade no contexto atual, articulando a produção vitivinícola a outros setores da economia, sobretudo o turismo.
Keywords: Indústria vinícula - São Roque (SP); Produtividade agrícola; Economia agrícola